Novel cytokine peptide-based vaccines: an interleukin-4 vaccine suppresses airway allergic responses in mice - Ma, Y; Hayglass, K.T; Becker, A.B; Halayko, A.J; Basu, S; Simons, F.E.R; Peng, Z (Allergy, 2007)
Monoclonal antibodies or soluble receptors have been used to block over-produced endogenous cytokines. However, they have disadvantages of short half-lives, high costs, and possible adverse effects. Using interleukin (IL)-4 as a model target, we sought to develop a novel therapeutic strategy by constructing an IL-4 peptide-based vaccine for blocking IL-4 on a persistent basis, and to evaluate its efficacy in a mouse model of asthma. A peptide was selected by antigenic prediction and structure analysis of IL-4/receptor complex. The vaccine was constructed by employing truncated hepatitis B core antigen as carrier with the peptide inserted using gene engineering methods. It was then expressed, purified and identified. Prior to intraperitoneal sensitization and intranasal challenge with ovalbumin, mice were subcutaneously immunized three times with the vaccine, or the carrier or saline as controls. Serum antibodies, inflammatory cells in bronchoalveolar lavage fluids (BALF), lung histology, and responsiveness to inhaled methacholine were analyzed. The vaccine presented as virus-like particles and reacted to polyclonal anti-IL-4 in Western blotting. Vaccinated mice produced high titers of IgG to IL-4. Serum ovalbumin-specific IgE, eosinophil accumulation in BALF, goblet cell hyperplasia, tissue inflammation and methacoline-induced respiratory responses were markedly suppressed in vaccinated mice with statistical significance, as compared with those in the control groups. Administration of this novel IL-4 vaccine led to an overall decrease in the development of airway allergic inflammatory responses. The results indicate that cytokine peptide-based vaccines hold potential for treatment of asthma and, by extension, other diseases where over-expressed cytokines play a pivotal role in pathogenesis.